The life cycle of a desert spider inferred from observed size frequency distribution - Nieto-Castañeda, Irma Gisela; Salgadougarte, Isaías Hazarmabeth; Jiménez-Jiménez, María Luisa (Instituto de Ecología, A.C., 2012)
We studied the life cycle of the spider Syspira tigrina (Araneae: Miturgidae) by indirect methods. This species is endemic to the North American deserts and locally abundant; nevertheless, information on its biology is scarce. We did monthly collections for over a year at La Paz, Baja California Sur, Mexico. We found that adult spiders were more abundant between August and November 2005 and had low abundance or were absent the remainder of the year while juveniles were present all year. To estimate changing body size structure of the population we analyzed juvenile tibia I length distribution (TIL) (as indicator of the body size) of each monthly sample by means of Kernel Density Estimators (KDEs). We found 35 TIL juveniles size groups (Gaussian components). The smallest juveniles were more abundant between October 2005 and January 2006 and the biggest were more abundant twice during the hottest months. We hypothesize that mating period is between August and October 2005 and the main recruitment period from November 2005 and January 2006. However we found evidenceof continuous recruitment through the year, suggesting that although there is a peak of reproduction in November, the females oviposit almost all year. Also there is evidence of juveniles’ growth pattern from January to July 2006. The use of KDEs with histograms is a very good statistical tool to delimit size groups with mixed frequency distributions that otherwise might be difficult. This tool should be useful to test any hypothesis related with the body size structure of a population or community.